2003
DOI: 10.1055/s-2003-38057
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthesis of Lavandulol via Indium/Palladium-Mediated Umpolung of Vinyloxirane

Abstract: A short synthesis of lavandulol is achieved by the In/Pdmediated reaction of isopropenyloxirane with 3-methylbut-2-enal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Alkyl-substituted allylic phosphates are suitable starting materials as well, underscored by the efficient and highly selective formation of 17 (>98% conv, 95% S N 2′, 92.5:7.5 er); subsequent treatment with MeLi delivered the tertiary alcohol, and concomitant removal of the acyl group revealed an irregular monoterpene derived from Artemisia annua L., from which the potent antimalarial artemisinin was isolated. 17 …”
Section: Resultsmentioning
confidence: 99%
“…Alkyl-substituted allylic phosphates are suitable starting materials as well, underscored by the efficient and highly selective formation of 17 (>98% conv, 95% S N 2′, 92.5:7.5 er); subsequent treatment with MeLi delivered the tertiary alcohol, and concomitant removal of the acyl group revealed an irregular monoterpene derived from Artemisia annua L., from which the potent antimalarial artemisinin was isolated. 17 …”
Section: Resultsmentioning
confidence: 99%
“…Koo et al [29] recently reported a stereoselective synthesis of S-8 from (R)-(-)-carvone (R-6) involving chemo selective but indirect deoxyg enation of allylic alcohol S-7 with retention of the homoallylic hydroxyl group (Scheme 7). Their method is superior in terms of ready availability of the starting material to other reported examples of racemic and stereoselective synthesis of lavandulol [28][29][30][31][32][33][34]. However, the key deoxygenation of S-7 to S-8 requires a tedious multi-step protection/deprotection sequence and stoichiometrically generates salt as a waste product [29].…”
Section: Application To (S)-(+)-lavandulol Synthesismentioning
confidence: 99%
“…The styrene epoxide and alkyl monosubsituted epoxides (17a) have undergone regioselective allylation with pregenerated allylindium reagent in dry THF to provide mixture of two possible homoallylic alcohols (18) and (19) with preferential nucleophilic attack at less substituted carbon (Scheme 5) [6]. In case of disubstituted terminal epoxides (17b) complete regioselectivity has been observed.…”
Section: Nucleophilic Additionsmentioning
confidence: 99%
“…The reaction has been extended to the synthesis of the lavandulol-a defensive pheromone of red lined carrion beetle and important constituent of perfume industry [19]. The coupling of isopropenyl oxirane (57b) and 3-methyl-but-2-enal (60) These reactions have demonstrated the umpolung of reactivity of aziridines as nucleophiles, which are conventially good electrophiles.…”
Section: Umpolung Of Reactivitymentioning
confidence: 99%